A novel mechanism for cytoprotection against hypoxic injury: δ‐opioid receptor‐mediated increase in Nrf2 translocation. (10th February 2015) - Cao, Shan; Chao, Dongman; Zhou, Honghao; Balboni, Gianfranco; Xia, Ying
Abstract : Background and Purpose: Hypoxia/reoxygenation induces synthesis of reactive oxygen species (ROS) which can attack macromolecules and cause brain injury. The transcription factor, nuclear factor (erythroid‐derived 2)‐like 2, (Nrf2), ia potent activator of genes with an antioxidant responsive element and Nrf2 can counteract oxidative injury by increasing expression of several antioxidative genes in response to ROS stress. Here, we show that activation of the δ‐opioid receptor (DOR) increasedNrf2 protein expression and translocation, thereby leading to cytoprotection. Experimental Approach: We used HEK293t cells exposed to 0.5% O2 for 16 h and then reoxygenated for 4 h as a model of hypoxia‐reperfusion (H/R) injury. Real time PCR, Western blotting, siRNA and immunohistochemical techniques were used to follow Nrf2 expression and activity. Cell viability and damage (as LDH leakage) were also measured. Key Results: H/R injury triggered Nrf2 translocation into the nucleus and up‐regulated expression of several downstream genes, relevant to antioxidation, such as NAD(P)H:quinone oxidoreductase ( NQO 1 ). Incubation with the DOR agonist UFP‐512 enhanced Nrf2 protein expression and translocation and up‐regulated its downstream genes in normoxia and further increased Nrf2 expression and translocation after H/R, protecting the cells against loss of viability and damage. The effect of UFP‐512 on Nrf2 nuclear translocation was blocked by the DOR antagonist, naltrindole. Also, DOR–mediated cytoprotection was strongly inhibited after transfection of HEK293t cells with Nrf2 siRNA. Conclusions and Implications: The DOR agonist UFP‐512 was cytoprotective against H/R injury and this effect was partly dependent on DOR‐mediated increase in Nrf2 function.